Atomization of glycerin with a twin-fluid swirl nozzle. (June 2017) - García, J.A.; Lozano, A.; Alconchel, J.; Calvo, E.; Barreras, F.; Santolaya, J.L.
Highlights: A twin-fluid swirl nozzle atomizing pure glycerin at room temperature is examined. Liquid ligaments observed near the nozzle exit break up while moving downstream. Mean droplet diameters below 20 µm can be obtained. In some conditions, 26% of the glycerin volume is in droplets smaller than 20 µm. Abstract: Atomization of liquids with high viscosity is always a challenge, especially when small diameter droplets and high liquid flow rates are simultaneously required. In the present research, the performance of a Venturi–vortex twin-fluid swirl nozzle is examined, attending to its capabilities to generate droplets with diameters below 20 µm when atomizing pure glycerin at room temperature. In this nozzle, air is injected tangentially in a central convergent section, and discharges suctioning the liquid fed to a coaxial chamber, here using a gear pump. The resulting spray is visualized and analyzed. Droplet size distributions are measured with a laser diffractometer. As expected, droplet diameter increases with liquid flow rate, and quickly diminishes when air flow rate is increased. Sauter mean diameters (SMD) below 15 µm can be obtained even when atomizing pure glycerin. However, these values are obtained for relatively low glycerin flow rates (∼5 l/h), and with rather wide distributions. For 10 l/h and an air-to-liquid mass flow rate ratio (ALR) of 13.7 more than 26% of the glycerin volume is atomized in droplets smaller than 20 µm. Liquid ligaments are observed near the nozzle exit, but they tend to break up while moving downstream.